Challenges and coping strategies of UP maninindas after the COVID-19 pandemic - Diaz, Danielle Vincci V.
This qualitative study investigated the challenges and coping strategies of University of the Philippines vendors (UP maninindas). Specifically, it described the challenges they faced after the pandemic, the coping strategies they adopted, and the perceived effectiveness of their coping strategies. Eight purposively selected street vendors in the University of the Philippines-Diliman were interviewed. Descriptive statistics and thematic analysis were utilized to analyze the data. The results showed that the most significant challenges faced by the maninindas after the pandemic include the rising cost of supplies, limited capital, lack of financial support from the government and institution, inconsistent face-to-face classes, and the increase of commercialized food shops around the campus. To mitigate these challenges, the UP maninindas had to develop several coping strategies in order to sustain their businesses. They employed pricing strategies, online selling, building customer relationships, improving and innovating products, and keeping up with the food trends. They also received support from the University Student Council, students, and UP alumni. Also, it was also found that the UP maninindas maintained cleanliness and food safety practices in order to gain more customers. Based on the given coping strategies, the UP maninindas mentioned that building personal relationships with their customers, improving their products, keeping up with food trends, maintaining cleanliness, and food safety practices were the most effective coping strategies. With the evolving landscape of the university environment, the study’s results underscore the importance for the community to provide continuous support to ensure the effective operation of UP maninindas’ businesses.